Systematic Literature Review Mindful Self Compassion Protocol - Thrisia Ferbrianti; Nabila Fuadina (Universitas Negeri Semarang, 2024)
Mindful Self-Compassion (MSC) is increasingly in demand for research and has shown effectiveness in improving psychological aspects in various fields. Thus, further studies are needed to see the MSC implementation protocol so that it can be applied effectively. This research focuses on the effectiveness of MSC in increasing self-compassion, mindfulness, life satisfaction, and reducing anxiety and stress. This research uses the Systematic Literature Review (SLR) method with search sources from Springer, Sagepub, Sciencedirect, and Wiley in the period 2019-2024. The selection process produced 8 articles based on predetermined inclusion criteria, namely articles that used mindful self-compassion interventions and used RCT experimental studies and quasi-experimental studies. Meanwhile, the exclusion criteria were articles that did not use MSC intervention as the main component and were not related to psychological and behavioral outcomes. The article search process is explained in the PRISMA Flow Diagram. MSC has been shown to be beneficial in the context of mental health in a variety of populations, including teachers, adolescents, caregivers of schizophrenia patients, women undergoing infertility treatment, young women, nursing students, and mothers of children with Phenylketonuria (PKU). Nevertheless, some studies show that the effects of MSCs do not always persist in the long term, indicating the need for further studies with longer follow-up periods. In conclusion, MSC is an effective intervention to improve psychological well-being, but further testing is needed to evaluate its long-term effects and optimize its application in various contexts. Mindful Self-Compassion (MSC) semakin diminati untuk diteliti dan telah menunjukkan efektivitasnya dalam meningkatkan aspek psikologis di berbagai bidang. Dengan demikian, diperlukan penelitian lebih lanjut untuk melihat protokol penerapan MSC agar dapat diaplikasikan secara efektif. Penelitian ini berfokus pada efektivitas MSC dalam meningkatkan self-compassion, mindfulness, kepuasan hidup, serta menurunkan kecemasan dan stres. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan sumber pencarian dari Springer, Sagepub, Sciencedirect, dan Wiley dalam kurun waktu 2019-2024. Proses seleksi menghasilkan 8 artikel berdasarkan kriteria inklusi yang telah ditentukan, yaitu artikel yang menggunakan intervensi mindful self-compassion dan menggunakan studi eksperimen RCT serta studi quasi eksperimen. Sedangkan kriteria eksklusi adalah artikel yang tidak menggunakan intervensi MSC sebagai komponen utama dan tidak terkait dengan luaran psikologis dan perilaku. Proses pencarian artikel dijelaskan dalam Diagram Alir PRISMA. MSC telah terbukti bermanfaat dalam konteks kesehatan mental pada berbagai populasi, termasuk guru, remaja, pengasuh pasien skizofrenia, wanita yang menjalani perawatan infertilitas, wanita muda, mahasiswa keperawatan, dan ibu dari anak-anak dengan Fenilketonuria (PKU). Meskipun demikian, beberapa penelitian menunjukkan bahwa efek MSC tidak selalu bertahan dalam jangka panjang, yang menunjukkan perlunya penelitian lebih lanjut dengan periode tindak lanjut yang lebih lama. Sebagai kesimpulan, MSC merupakan intervensi yang efektif untuk meningkatkan kesejahteraan psikologis, tetapi pengujian lebih lanjut diperlukan untuk mengevaluasi efek jangka panjangnya dan mengoptimalkan penerapannya dalam berbagai konteks.